PERSEPSI PERHELATAN, KEPUASAN TERHADAP PERHELATAN, DAN SIKAP TERHADAP MEREK RITEL: SEBUAH STUDI EMPIRIS - Alexander Joseph Ibnu Wibowo (Universitas Bunda Mulia, 2017)
The study aims to test the relation among event perception (event inventiveness, event appropriateness, and event adequacy), event satisfaction, and attitude toward retail’s brand. A structured questionnaire was designed to collect the data. Multiple and simple linear regression techniques were used to test the causal relations of four hipotesis proposed. The results showed that both event adequacy and event inventiveness affect event satisfaction. Nevertheless, event appropriateness did not affect event satisfaction. Afterwards, event satisfaction influenced attitude toward retail’s brand. The contribution of this study was through empirical verification concerning the prior model designed by Leischnig, Schwertfeger, and Geigenmueller (2011). Empirical contribution came from the findings of the strength of relationship between variables tested. Besides theoretical contribution, this study also delivered practical contribution for event organizer.Keywords: Perception, Satisfaction, Attitude, Event, Marketing